LOTION PROTECTIVE EFFECT USING LEMONGRASS ESSENTIAL OIL (Cymbopogon citratus) AGAINST Aedes aegypti - Ainun Sida; Ni Luh Arpiwi; Anak Agung Ketut Darmadi (Jurnal Biosains Pascasarjana, 2023)
Lemongrass consists of two types that have many benefits. Its use in research or in processing using its stems alone causes lemongrass leaf waste which can be used as an essential oil and used as an anti-mosquito lotion to reduce the use of chemicals as repellent. The purpose of this study was to determine the yield of lemongrass essential oil, to determine the protective power of each concentration of citronella essential oil in lotion in repelling mosquito bites, and to determine the level of preference for mosquito repellent lotion. The average yield with three repetitions followed by standard deviation (SD) was 0.1% ± 0.0024% b/b. Lotion preparation provides different protection during 6 hours of exposure, namely K- and F1 no protection, F2 for 2 hours, F3 and K+ 4 hours and F4 5 hours. Based on all parameters, the most preferred formulation is F1 and does not give sensitive reactions. Keyword: Aedes aegypti, essential oils, lemongrass, lotions.